2020
DOI: 10.1038/s41598-020-58265-3
|View full text |Cite
|
Sign up to set email alerts
|

Coherent response of the Indian Monsoon Rainfall to Atlantic Multi-decadal Variability over the last 2000 years

Abstract: Indian Summer Monsoon (ISM) rainfall has a direct effect on the livelihoods of two billion people in the indian-subcontinent. Yet, our understanding of the drivers of multi-decadal variability of the iSM is far from being complete. In this context, large-scale forcing of ISM rainfall variability with multi-decadal resolution over the last two millennia is investigated using new records of sea surface salinity (δ 18 Ow) and sea surface temperatures (SSts) from the Bay of Bengal (BoB). Higher δ 18 Ow values duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…However, the phase arrows in the significant area in the high-frequency region during 1950-2016 are randomly oriented, so its manifestation is not clear. The correlation between AMO and rainfall variability during 1960-2006 is consistent with Naidu et al [16]; however, the two records have not precisely matched temporally.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…However, the phase arrows in the significant area in the high-frequency region during 1950-2016 are randomly oriented, so its manifestation is not clear. The correlation between AMO and rainfall variability during 1960-2006 is consistent with Naidu et al [16]; however, the two records have not precisely matched temporally.…”
Section: Discussionsupporting
confidence: 83%
“…Like PDO, the AMO is the pattern of SSTs in the North Atlantic Ocean with periodicities of 55-80 years [62]. The AMO has been suggested to play a significant role in modulating ISMR on a decadal to a multi-decadal scale [14][15][16]. In a study, Malik et al [15], using a long data record of 400 years, reported that the modulation of ISMR on a decadal to multi-decadal scale has influenced by the integrated effect of AMO, PDO, and TSI (Total Solar Irradiance).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal contrast between the Indian subcontinent and the Indian Ocean drives the Indian monsoon circulations (Naidu et al., 2020; Roxy et al., 2015; Schott & McCreary, 2001; Wu et al., 2012). The southwest Indian monsoon (SW monsoon, Figure ) typically peaks in boreal summer (July and August) and provides most of the total annual rainfall on the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%